Etnografía, improvisación y narrativas digitales - Ramos Mancilla, Oscar (2022)
This paper presents some ideas related to the difficulties that may happen during the fieldwork and that may urge us to improvise in order to be able to continue with our ethnographic research. However, these decisions must consider the implications of improvisation in terms of knowledge production and specifically in methodological planning. To support these reflections, presents a fieldwork situation in which digital narratives were useful for rapport and to complement the field data. Thus, a remarkable aspect is that the reflection on improvisation in our ethnographic practice can lead us to an intentional experimentation that helps us to enlarge the robust methodological baggage of ethnography.